A Comparative Study of Surface Plasmon and Tamm Plasmon Polaritons for Hydrogen Sensing - Almeida Miguel A.S.; Carvalho João P.M.; Pastoriza-Santos Isabel; Almeida José M.M.M.; Coelho Luís C.C. (EPJ Web of Conferences, 2024)
Due to the exponential increase in energy consumption and CO2 emissions, new sustainable energy sources have emerged, and hydrogen (H2) is one of them. Despite all the advantages, H2 has high flammability, so constant monitoring is essential. Two optical techniques were numerically studied and compared with the goal of H2 sensing: surface plasmon polaritons (SPP) and Tamm plasmon polaritons (TPP). The H2-sensitive material used was palladium (Pd) in both techniques. The SPP structure was found to have more sensitivity to H2 than TPP, 23 and 5nm/4vol% H2, respectively. However, the latter has lower FWHM, with the minimum of the band showing reflectivity near 0%. In addition, TPP also uses more costeffective materials and can be interrogated at normal incidence with depolarized light. The potential of using each of these optical techniques for H2 sensing was demonstrated.